Comparison between professional sampling and self‐sampling for HPV‐based cervical cancer screening among postmenopausal women - Bergengren, Lovisa; Kaliff, Malin; Larsson, Gabriella L.; Karlsson, Mats G.; Helenius, Gisela (International journal of gynecology and obstetrics, 2018)
Objective To investigate whether self‐sampling is as reliable as professional sampling for HPV testing and genotype detection among postmenopausal women. Methods In the present prospective cross‐sectional study, women in Örebro County, Sweden, who had high‐risk HPV (hrHPV) and normal cytology results in exit screening tests conducted in between January 1, 2012, and December 31, 2014, were invited to follow‐up screenings between February 24, 2015 and May 15, 2015, that included professional sampling and self‐sampling. HPV genotypes were identified by a DNA‐based assay that could detect 35 HPV genotypes. Findings between the different sampling methods were compared. Results Of 143 women who participated, 119 returned a self‐sample. Completely concordant results were observed in 67 of these samples when both hrHPV and low‐risk HPV genotypes were analyzed. Overall, 99 (83.2%) women had the same clinically relevant finding from both sampling methods. Twenty women had discordant hrHPV results (hrHPV detected in 10 self‐samples vs 10 professionally collected samples; Cohen κ 0.66, 95% confidence interval 0.53–0.80). There was no significant difference between the two sampling methods for clinically significant infections (P>0.99) or extended genotyping (P=0.827). Conclusion Postmenopausal women could be offered self‐sampling devices to increase screening‐program coverage while maintaining test quality. The concordance between professionally and self‐collected HPV‐testing samples was 83%. Postmenopausal women could be offered self‐sampling without loss of test quality.